Book and Libraries in the Ancient World: Celsus Library in Ephesus - Zehra Taşkın (Türk Kütüphaneciliği)
There were many ancient civilizations during history and each civilizations left indelible marks. The main aim of this study is to evaluate Ephesus and its Celsus Library. Ephesus did the honors for many important civilizations in history and it was a connector between east and west. As a consequence Ephesus and Celsus library have importance on history.